Digital Pedagogy Philosophy: Building Critical Awareness of The Role of Technology in Education - Fadli, Muhammad Rijal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
Technology integration in education raises the need for a philosophical foundation that guides the use of technology in learning contexts. The philosophy of digital pedagogy is an approach that provides an ethical basis and values that guide the application of technology in the educational process. This paper aims to explore the relationship between digital pedagogical philosophy, critical consciousness, and the role of technology in shaping contextual and adaptive learning experiences. This research uses a hermeneutic approach to describe the reality of Digital Pedagogical Philosophy in building critical awareness of the role of technology in education. This method involves elements of interpretation and description in analyzing and understanding the implications and significance of technology integration in the learning context. The philosophy of digital pedagogy provides a foundation for integrating technology into learning to support the formation of critical, creative, and responsible individuals. Critical awareness of the role of technology in education creates a deeper understanding of the challenges and opportunities faced in the digital environment. This approach can increase student interaction with course material, increase understanding of concepts, and promote critical thinking.